Heterogeneity of a Tree Species Community in an Alluvial Area of Santa Catarina, Brazil - Goncalves D.A.* (2018)
© Creative Commons License. All the contents of this journal, except where otherwise noted, is licensed under a Creative Commons Attribution License.The aim of the present study was to characterize the floristic-structural heterogeneity of the tree species in an alluvial forest remnant considering three sectors: forest-river edge, forest interior and forest/non-forest matrix edge. Forty-eight plots of 200 m2 were allocated and all tree individuals with a diameter at breast height (dbh) equal to or greater than 5 cm were measured an identified. Data was analyzed by Shannon’s diversity index, Pielou evenness and phytosociological descriptors. Plots were ordered through NMDS. Sixty-six species were sampled and Myrtaceaewas found to be the richest family. Diversity and evenness reached 2.96 and 0.71, respectively. Sebastiania commersoniana (Baill.) L.B.Sm. & Downs presented the highest importance value (21.22%). The NMDS showed that tree components are spatially partitioned according to sectors, therefore indicating floristic-structural heterogeneity